Kompetensi Lulusan SMK Program Studi Teknik Otomotif Sesuai Dengan Tuntutan Revolusi Industri 4.0 : Kajian Literatur - Toto Sugiarto; Nizwardi Zalinus; Refdinal Refdinal; Wawan Purwanto; Ahmad Arif (AEEJ : Journal of Automotive Engineering and Vocational Education, 2022)
The purpose of this study was to identify the competencies of graduates of the Automotive Engineering Vocational High School, in accordance with the demands of the Industrial Revolution 4.0, who must have abilities in accordance with technological developments and the needs of the business and industrial world (DUDI). The research method was carried out by means of Literature Study. Based on the results of the study and analysis, the competencies that must be mastered by SMK graduates in the automotive engineering study program so that they are in accordance with the needs of DU/DI and the demands of the industrial revolution 4.0, must have two competencies, namely Soft Skill competencies and Technical Competences. Entrepreneurial Spirit Soft Skill Competence, which has: (1) Leadership spirit, (2) Able to understand digital technology, (3) Mastery of communication and information media, (4) Able to control emotions, (5) Creative, and Innovative, (6) Have broad insight, (7) Ability to think critically and be able to solve problems, (8) Able to collaborate and work in teams, (9) Able to understand cultural and cultural differences, (10) Able to develop a career and be confident. Tujuan penelitian ini adalah untuk mengidentifikasi kompetensi lulusan Sekolah Menengah Kejuruan Program Studi Teknik Otomotif, sesuai dengan tuntutan Revolusi Industri 4.0, yang harus memiliki kemampuan sesuai dengan perkembangan teknologi dan kebutuhan dunia usaha dan dunia industri (DUDI). Metode penelitian dilakukan dengan Studi Literatur. Berdasarkan hasil kajian dan analisis, kompetensi yang harus dikuasai oleh lulusan SMK program studi teknik otomotif supaya sesuai dengan kebutuhan DU/DI dan tuntutan revolusi industri 4.0, harus mempunyai dua kompetensi, yaitu kompetensi Soft Skiil dan Kompetensi Teknis. Kompetensi Soft Skill jiwa kewirausahaan, yang memiliki: (1) Jiwa kepemimpinan, (2) Mampu memahami teknologi digital, (3) Menguasai media komunikasi dan informasi, (4) Mampu mengendalikan emosi, (5) Kreatif, dan Inovatif, (6) Mempunyai wawasan Luas, (7) Kemampuan berpikir kritis dan bisa memecahkan masalah, (8) Mampu berkolaborasi dan bekerja dalam tim, (9) Mampu memahami perbedaan kultur dan budaya, (10) Mampu mengembangkan karir dan percaya diri.